Analysis Of Library Saleh Adiwinata User Satisfaction Using The LibQual+TM Method - Atikah, Lilis; Anshori, Irfan Muhajirin (Indonesian Journal of Librarianship, 2023)
Background: The level of user satisfaction serves as an indicator of the effectiveness and overall performance of a library. The provision of high-quality library services plays a crucial role in attaining customer satisfaction. Quality services have the potential to deliver favorable experiences to users, enhance the accessibility of library collections, and effectively address the information requirements of users. Purpose: The aim of this study is to assess overall user happiness as well as user satisfaction across various dimensions of the LibQual+TM framework Method: The research methodology employed in this study is a quantitative survey method. The utilized tools align with the characteristics of the LibQual+TM technique, specifically Affect of Service, Information Control, and Library as Place. The sample parameters were determined by the utilization of accidental sampling, resulting in a total sample size of 86 respondents. Result: The study of the Adequacy Gap (AG) revealed a score of 0.199, while the investigation of the Superiority Gap (SG) yielded a value of -0.216. Moreover, in terms of the dimension of Service Affect, the gap score for AG is 0.195, while for SG it is -0.181. On the dimension of Information Control, the AG score is 0.217, whereas the SG score is 0.395. During the assessment of the Library as Place dimension, the AG score was determined to be 0.163, while the SG score was found to be 0.172. Conclusion: The findings indicate that users express a high level of satisfaction with the service quality provided by the Saleh Adiwinata Library. Furthermore, users perceive the service quality to be of good standard, falling within acceptable boundaries. The optimal sequence of dimensions that most effectively align with user expectations includes Information Control, Affect of Service, and Library as a Place. Keywords: User Satisfaction; LibQual+TM; Affect of Service; Information Control; Library as a Place